Adobe Creative Suite 6 introductory - Starks, Joy; Fehl, Alec (Shelly Cashman series, 2013)
Follows the proven approach to learning the Photoshop[Registered], Flash[Registered], and Dreamweaver[Registered] CS6 software. In this text, you can find features designed to engage students, improve retention, and prepare them for future success. It can have students learn by doing, not just reading